Persepsi Ruang Pada Interior Restoran Donwoori Bandung - Hadiansyah, Mahendra Nur; Hendrawan, Alvin Sofyan (Waca Cipta Ruang, 2020)
Restaurant Donwoori is a Korean-themed cafÃ© and restaurant located on the street Lombok, Bandung. Korean Drama becomes a theme in interior design because have a storyline which make the audience feelings mixed between happy and sad. This research aims to find out how the role of Korean Drama becomes a reference in attractive interior design style and also realizing Korean thematic in room. The method carried out qualitatively in from of data collection, observation, documentation, and interviews with visitor. The results show that the use of Korean drama nuances to influence interior style that exist at Donwoori restaurant. Each section has a variant function and interior elements to form the atmosphere of Korean drama such a cutlery, decorative elements, ceiling, lightning, color, application and furniture. The form of interior implementation is carried out towards interior elements utilizing Korean drama series background with the genre of romantic comedy teenager which is loved by many people